Risk/Return Performance of Diversified Firms - Bettis, Richard A.; Mahajan, Vijay (Management Science, 1985)
Based on a sample of 80 firms, this paper examines the risk/return performance of related and unrelated diversified firms at the level of accounting data. The results suggest that although on the average related diversified firms outperform unrelated diversified firms, related diversification offers no guarantee of a favorable risk/return performance. (Many low performers are related diversifiers.) In fact, different diversification strategies can result in similar risk/return performance. However, a favorable risk/return performance is extremely hard to achieve with unrelated diversification. The study identifies diversified firms that have managed to simultaneously reduced risks and increase returns. The results indicate that these firms differ from other firms on some managerially useful dimensions. The differences suggest clues to guide other diversified firms to improve their risk/return performance.